СОВРЕМЕННЫЕ ПРОБЛЕМЫ ГЕОМЕХАНИКИ В УГОЛЬНОЙ ОТРАСЛИ - Яковлев Д.В.; Розенбаум М.А. (My University, 2006)
В соответствии с постановлением Правительства в России с 1994 г. осуществляется реструктуризация угольной отрасли с техническим переоснащением перспективных угледобывающих предприятий, сооружением шахт и разрезов нового технического уровня при одновременном закрытии особо убыточных и опасных по условиям работы шахт. Главной целью реструктуризации объявлено создание конкурентоспособного эффективного производственного комплекса, обеспечивающего удовлетворение спроса на уголь, при резком снижении затрат на его добычу, улучшение безопасности работ и экологии. Новые преобразования в технологии угледобычи потребовали и решения новых геомеханических задач, перечень которых приведен в статье.

In accordance with the decision of the Government in Russia since 1994 the coal industry restructuring is being carried out together with the technical reequipment of promising coal-mining plants, construction of mines and open-pit mines of new technical level along with the simultaneous abandonment of rather unprofitable and dangerous mines. The main objective of restructuring is the creation of competitive efficient production complex meeting the demand for coal, with abrupt decrease of expenses for its output providing better safe mining operations and ecological conditions. New transformations in the coal mining technology will entail also the solutions of new geomechanical tasks, which the authors present in this Arcticle.
Keywords: 622.016.22+622.268.12